(untitled) (LACCEI, 2024)
In the present investigation, the adsorption of copper, iron and mercury in solution with concentrations of 100, 300 and 500 ppm was evaluated in the seaweed Chondracanthus chamissoi "cochayuyo" during agitation times of 2, 4 and 6 hours, following the multiple factorial design and according to the analysis of variance of the data obtained as results, the most significant variable was the agitation time, which corresponded to a first order kinetics of adsorption of metals in solution in the seaweed. The least significant variable was the concentration of the test solutions. The metals copper, iron and mercury dissolved in the same volume of solution were adsorbed in higher amount when the algae weight was lower, compared to the lower amount adsorbed for higher algae weight. There was not much difference between the adsorption rate behavior by the algae at the same test conditions, being first iron, then very close copper and then mercury. The highest average weight of copper, iron and mercury deposited on Chondracanthus chamissoi was 78.4, 85.6 and 70.8 µg/g of algae respectively and corresponded to an agitation time of 6 hours, with 10 g of algae in the column and 500 ppm of copper, iron and mercury solution respectively. The lowest average weight of copper, iron and mercury deposited on Chondracanthus chamissoi was 43.8, 38.8 and 32.6 µg/g of algae respectively and corresponded to an agitation time of 2 hours, with 30 g of algae in the column and 100 ppm in copper, iron and mercury solution respectively. Based on these results, which show the feasibility of adsorption of metals present in a solution on the surface of the algae, biofilters with Chondracanthus chamissoi can be used for the treatment of Acid Mine Drainage (AMD), effluents from artisanal or other mining activities that generate liquid waste with the presence of heavy metals, designing the appropriate equipment for the treatment of effluents containing these dissolved metals, using Chondracanthus chamissoi as a biosorbent.